(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article discusses the importance of developing labor skills and abilities in preschool children as an essential factor in preparing them for school education. The pedagogical conditions, methods, and forms of organizing labor activities in preschool educational institutions are highlighted. Particular attention is given to the development of independence, responsibility, diligence, and teamwork skills in children. It is emphasized that the proper organization of labor education contributes to the comprehensive development of a child’s personality and facilitates successful adaptation to school learning.